Feeling Blue: Officer Perceptions of Public Antipathy Predict Police Occupational Norms - Marier, Christopher J. (American journal of criminal justice, 2019)
Recent protests against law enforcement have spurred claims by practitioners and editorialists that public antipathy toward the police may influence police occupational norms. A number of classic police ethnographies also suggest a link between perceived public antipathy and police culture, but limited empirical research has examined this claim. Using a sample of 12,376 sworn law enforcement officers who participated in the National Police Research Platform, and a series of ordinary least squares regressions, this study examines whether officers’ perceptions of public support predict their cultural orientations. Results reveal that officers perceiving greater public antipathy report higher levels of social isolation, work-group solidarity, cynicism toward the public, and coercive attitudes. We identify practical implications and potential organizational remedies to address these perceptions, and situate these findings within theoretical arguments of early police ethnographers and contemporary claims of the “Ferguson Effect.”